Precision Medicine for Neurofibromatosis Type 1: Progress and Prospects in Drug Discovery - Sheilina Choudhary (International Journal of Bioinformatics and Computational Biology, 2024)
Objective: The development of neurofibromas, café-au-lait spots, and other neurological problems are the hallmarks of neurofibromatosis type 1 (NF1), a hereditary disorder. The dearth of efficacious pharmaceutical therapies underscores the need for novel therapeutic approaches, even in the face of clinical variability. Through very accurate prediction of the binding affinity of possible therapeutic drugs with the target protein, the computational technique known as “molecular docking” has become a potent tool in the drug development process. In the context of NF1 drug discovery, this research work intends to investigate the use of molecular docking. Using molecular docking techniques, the main goal of this work was to find tiny molecules or compounds that could control important proteins implicated in NF1 pathogenesis. Through a comprehensive literature review, relevant protein targets associated with NF1, such as neurofilament and its interacting partners, will be identified and selected for molecular docking studies. Virtual screening of complex libraries will be performed using state-of-the-art docking algorithms to predict binding affinities and modes of interaction between potential drugs and target proteins. Furthermore, this study aimed to confirm the effectiveness of lead compounds identified through SWISS ADMET (absorption, distribution, metabolism, excretion, and toxicity) analysis to assess their drug similarity and safety profile. The results of this research effort have the potential to accelerate the discovery and development of new treatments for NF1, bringing new hope to patients with this debilitating genetic disease. Methods: In this study, target proteins were downloaded from PDB and docked into BIOVIA. The binding affinity of standard and drug ligands to each target protein was compared and evaluated. Additionally, only four substances were selected for the final SWISS-ADME results. Results: When two molecules are coupled together to create a stable complex, the docking result predicts the preferred orientation of one molecule (the ligand) to the other (the target protein). Conclusion: These ligands could potentially be used for the treatment of neurofibromatosis type 1 in future approaches to study the necessary ligands in vitro and analyze them in vivo for the generation of new neurofibromatosis inhibitors.
Keywords: Attention-deficit hyperactivity disorder; Cafe-au-lait spots; Malignant peripheral nerve-sheath tumors; NF1 gene; NF1 gene mutation; Neurofibromatosis; Neurofibromatosis Tumors; Neurofibromin; Tumor suppressor gene; and Kinase Inhibitors; molecular docking